1992
DOI: 10.1159/000187090
|View full text |Cite
|
Sign up to set email alerts
|

Potential Deleterious Effect of Furosemide in Radiocontrast Nephropathy

Abstract: The purpose of the study was to determine the efficacy of furosemide in addition to intravenous fluids in the prevention of radiocontrast nephropathy. 18 patients, referred to a radiocontrast study, considered at risk because of preexisting renal insufficiency, were enrolled in a prospective, randomized, controlled trial, performed at the secondary care center of a 1,100-bed private university hospital. In addition to fluids, the treatment group received furosemide (mean dose 110 mg) intravenously 30 min prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(70 citation statements)
references
References 3 publications
3
64
0
3
Order By: Relevance
“…These actions provide a foundation for several prophylactic efforts to prevent or reduce contrast media induced nephropathy, including hydration and the administration of furosemide, mannitol, calcium channel blockers, dopamine, atrial natriuretic peptide and theophylline [2,19,25]. The etiology and pathophysiology of contrast media induced nephropathy have not made clear, so optimal prevention from contrast media induced nephropathy in high risk Fig 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These actions provide a foundation for several prophylactic efforts to prevent or reduce contrast media induced nephropathy, including hydration and the administration of furosemide, mannitol, calcium channel blockers, dopamine, atrial natriuretic peptide and theophylline [2,19,25]. The etiology and pathophysiology of contrast media induced nephropathy have not made clear, so optimal prevention from contrast media induced nephropathy in high risk Fig 4.…”
Section: Discussionmentioning
confidence: 99%
“…In group 1 (A) and group 2 (B) only nephrograms were performed but in group 3 (C) the pyelogram was shown and the renal recess could be identified. patients has not been yet well defined [25]. It has already been shown that dehydration potentiates the vasoconstrictive effects of contrast media and some investigators have attempted to reduce the likelihood of contrast media induced nephropathy by pretreatment with volume expansion or diuresis [17,21].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous hydration with 0.9% SS) 0.9% SS 1 mL/kg/h, 12 hours before and 12 hours after the procedure Several randomized studies and metaanalyses 30,[32][33][34] 0.9% SS is superior to 0.45% SS 23,32 Sodium bicarbonate (154 mEq/L) NaHCO3 3 mL/kg/h, 1 hour before the procedure and 1 mL/kg/h, 6 hours after the procedure Several randomized studies and meta-analyses 32,[49][50][51][52][53][54] Dilute 154 mL of 8.4% sodium bicarbonate in 846 mL of distilled water for obtaining the solution Type of contrast medium Low-osmolality or iso-osmolality contrast medium Some randomized studies and a few meta-analyses [26][27][28] The literature is still controversial whether isoosmolality contrast medium is superior to low-osmolality contrast medium 29 N-acetyl cysteine 600 mg, orally, 12/12 hours, 24 hours before and after the procedure Still controversial 54,55 Large ongoing multicenter study 56 …”
Section: Most Used Methods Evidence Level Commentsmentioning
confidence: 99%
“…30 However, a recent study with 5,256 patients undergoing coronary angiography, has found a paradoxical result: the increase in the contrast medium volume associated with the reduction in the incidence of CN. In patients receiving < 115 mL of contrast medium, the incidence of CN was 16%; in those receiving from 115 to 160 mL, it was 14%; in those receiving from 161 to 225 mL, it was 8%; and, finally, in patients receiving > 225 mL, it was 7%.…”
Section: Volume Of Contrast Medium Usedmentioning
confidence: 99%
See 1 more Smart Citation